Design-Based Research - A Research Format for Educational Research (Journal of Contemporary Educational Policies and Practices, 2025)
In educational research, the gap between university research and school practice is frequently pointed out. Particularly, the transfer of innovative scientific research findings into teaching practice occurs far too rarely or too late. Although theorists and teachers recognize and criticize the problem of theory-practice transfer, there are still few convincing concepts of how to sustainably address this challenge. The Design-Based Research approach offers a way to bridge the gap between theory and practice. Design-Based Research combines scientific theory, empirical research, and school practice. In this research format, scientists and teachers collaboratively develop theory-driven and practically tested teaching concepts or learning materials through iterative research cycles. Design-Based Research projects aim to find practical solutions to the challenges that have been identified in teaching. Design-Based Research not only facilitates the development of solutions for teaching practice, but it also generates contributions to subject-specific didactic theory through the research process. A significant advantage of Design-Based Research is that the results of a Design-Based Research project can be implemented in the classroom more quickly, due to the close cooperation between theorists and practitioners. The paper demonstrates the implementation of Design-Based Research in Geography Education through a case study on Africa.
Keywords: Design-Based Research; Africa; spatial perception; qualitative research; theory-practice connection